More hype than hope: Hydrogen policy, projects and environmental conflicts - Beatrice Negro; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2025)
Hydrogen plays a central role in policies aimed at decarbonisation, energy autonomy, industrial competitiveness, and development. This study analyses hydrogen policies, revealing how their design may undermine just transition goals and instead reinforce existing spatial inequalities. Drawing on International Energy Agency (IEA) data on clean hydrogen projects, investment trends are examined. A spatial analysis combining project data with environmental conflicts, sourced from the Atlas of Environmental Justice, reveals a concentration of hydrogen projects in areas affected by ecological degradation and socio-environmental disparities, raising concerns about the socio-ecological distributive effects. Hydrogen development appears largely driven by market logics and seems unlikely to meet climate targets.
Keywords: Q42; Q56; R11; 330; energy transition; industrial policy; hydrogen policy; environmental justice